Conversational Analysis of Politeness Strategies in Tom Lembong’s Political Podcast Interview - Nidiya Mawarni; Dwi Putri Lestari; Krisna Weny; Jamaluddin Nasution (Program Studi Pendidikan Bahasa Inggris, Universitas Pendidikan Muhammadiyah Sorong, 2026)
This study investigates how politeness strategies and conversational structures shape Tom Lembong’s political communication style in the What Is Up, Indonesia? podcast. Integrating Leech’s (2014) Politeness Principle and Yule’s (1996) Conversational Analysis (CA), the research aims to identify the types of politeness maxims employed and examine how conversational features contribute to constructing Tom’s political persona. Using a qualitative descriptive approach, the data were drawn from Tom Lembong’s utterances in a 40-minute YouTube interview. The analysis identified seven politeness maxims, with the Agreement Maxim occurring most frequently (22), followed by Approbation (11), Opinion Reticence (11), Tact (10), Modesty (10), Sympathy (5), and Feeling Reticence (4). Conversational features were also found throughout the interaction, dominated by Feedback (12), Turn-Taking (8), Repair (8), Sequence (6), and Action Formation (5). The findings reveal that Tom’s political persona is constructed through the synergy of politeness and conversational organization. His frequent use of agreement, praise, humility, and cautious opinion expression, combined with smooth turn-taking, responsive feedback, and effective repair, produces an image of a calm, respectful, and approachable political figure. This study contributes to digital political discourse research by demonstrating that politeness is not only reflected in lexical choices but also embedded in interactional structure. It further shows how political identities are strategically shaped in contemporary online media, suggesting opportunities for future comparative studies across different political actors and platforms.